Ceramic articles and methods for making same

By introducing high-density and low-porosity areas into the ceramic support and adjusting the load amount of catalytic active substances, the problem of excessive loading in existing catalysts is solved, and the optimization of catalyst volume and cost reduction is achieved.

JP7667277B2Active Publication Date: 2025-04-22SAINT GOBAIN CERAMICS & PLASTICS INC

Patent Information

Application Number
JP2023536820
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-29
Filing Date
2021-12-17
Publication Date
2025-04-22
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

The loading of catalytic active substances in existing catalysts is too high, resulting in the catalyst occupying too much space in the reactor, increasing costs and reducing economics.

Method used

By introducing high-density and low-porosity areas into the ceramic support, the loading of the catalytic active substances is adjusted to optimize the catalyst volume.

Benefits of technology

The catalyst occupies space in the reactor, reduces the cost of the catalyst usage, and maintains the primary performance of the catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667277000005
    Figure 0007667277000005
  • Figure 0007667277000006
    Figure 0007667277000006
  • Figure 0007667277000007
    Figure 0007667277000007
Patent Text Reader

Abstract

A ceramic article, such as a catalyst support, is disclosed that includes a continuous matrix and a dispersed phase distributed within the matrix as a plurality of discrete regions. The matrix and the discrete regions have different dye penetration test values. The disclosure also relates to methods of making and characterizing the ceramic article, and to catalyst bodies that include the ceramic article.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure generally relates to a ceramic article including a plurality of first alumina particles forming a continuous matrix and a plurality of second alumina particles dispersed within the matrix, the first and second alumina particles having different dye penetration test values. The present disclosure also relates to a catalyst incorporating a catalytically active material on a surface of the ceramic article. Summary of the Invention [Problem to be solved by the invention]

[0002] Catalysts are generally made by impregnating a support, typically a ceramic article made of ceramic material, with a catalytically active material, such as a metal. In certain aspects, a catalyst with too high a weight ratio of catalytically active material to support may be undesirable. For example, even if a catalyst has a long life due to a high loading of catalytically active material, it may be very expensive and economically unfeasible when used in a reactor where a low catalyst loading per unit volume in the reactor is desired. Thus, there is a need in the art for a ceramic support for catalysts where the structure of the ceramic support allows for the adjustment of the loading of active catalytic material in the catalyst body.

[0003] The present disclosure relates to a ceramic article comprising a hard formation of alumina particles. The hard formation comprises a plurality of first alumina particles and a plurality of second alumina particles. Both plurality of particles are randomly distributed throughout the hard formation. The second alumina particles have a ZnI2 dye penetration test value of 5 atomic percent or less, and the first alumina particles have a ZnI2 dye penetration test value that is at least twice the ZnI2 dye penetration test value of the second alumina particles. The hard formation has a total cross-sectional area. Each of the plurality of particles occupies a portion of the total cross-sectional area, and the cross-sectional area of ​​the second alumina particles is between 5% and 50% of the total cross-sectional area.

[0004] In some aspects, the ceramic article embodiment has a ZnI2 dye penetration test value of the dispersed phase (i.e., the second alumina powder) that is lower than the ZnI2 dye penetration test value of the continuous matrix (i.e., the first alumina powder). One embodiment relates to a ceramic article in which the ratio of the dye penetration test value of the first alumina particles to the dye penetration test value of the second alumina is at least 2:1. One embodiment relates to a ceramic article in which the dye penetration test value is obtained by a method including one or more of scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). One embodiment relates to a ceramic article in which the penetration test value is determined by a ZnI2 dye penetration test. One embodiment relates to a ceramic article in which a plurality of first alumina particles forming a continuous matrix have a ZnI2 dye penetration test value of 10 atomic percent or more. One embodiment relates to a ceramic article in which a plurality of second alumina particles forming a dispersed phase have a ZnI2 dye penetration test value of 5 atomic percent or less.

[0005] In some aspects, embodiments of the ceramic article have a thickness of about 0.2 cm 3 / g ~ approx. 0.7cm 3 / g. One embodiment has a total pore volume of about 0.3 cm 3 / g ~ approx. 0.6cm 3 / g. In one embodiment, the ceramic article has a total pore volume of about 0.35 cm 3 / g ~ approx. 0.5cm 3 / g. One embodiment relates to a ceramic article having a total surface area of ​​about 0.4 m 2 / g ~ approx. 3m 2 / g. One embodiment relates to a ceramic article having a total surface area of ​​about 0.4 m 2 / g ~ approx. 1.5m 2 / g. One embodiment relates to a ceramic article having a total surface area of ​​about 0.5 m 2 / g~approx.0.85m 2 / g for the ceramic article.

[0006] The present disclosure also relates to a metal-based catalyst body comprising a metal deposited on a ceramic article as described herein. One embodiment relates to a catalyst body in which the metal is silver. One embodiment relates to a catalyst body comprising silver deposited on a ceramic article, the ceramic article comprising a continuous alumina matrix and a dispersed alumina phase distributed within the continuous alumina matrix as a plurality of discrete regions, the article being 0.3 cm 3 / g~0.6cm 3 / g and the total pore volume of 0.5m 2 / g~0.85m 2 / g, wherein the continuous alumina matrix has a ZnI2 dye penetration test value of 10% or greater and the dispersed alumina phase has a ZnI2 dye penetration test value of 5 atomic percent or less, and the dispersed alumina phase covers 5% to 50% of the cross-sectional area of ​​the ceramic article.

[0007] One embodiment relates to a method for making a ceramic article, wherein the first plurality of alumina particles and the second plurality of alumina particles comprise alpha-alumina. One embodiment relates to a method for making a ceramic article, wherein the second plurality of alumina particles comprise fused alumina. One embodiment relates to a method for making a ceramic article, wherein the second plurality of alumina particles comprise platelet alumina. One embodiment relates to a method for making a ceramic article, comprising a bond material, wherein the bond material is magnesium silicate. [Brief description of the drawings]

[0008] The foregoing summary, as well as the following detailed description of the invention, will be better understood when read in conjunction with the appended drawings. [Figure 1] FIG. 1 shows the surface area and water absorption of a ceramic article as a function of the amount of dispersed phase. [Figure 2A] FIG. 2A shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 2B] FIG. 2B shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 2C]FIG. 2C shows the microstructure of an article of the present invention at magnifications of 100×, 250×, and 500×, respectively. [Figure 3A] FIG. 3A shows an SEM image of an article of the invention that was mounted in epoxy, cross-sectioned, and polished to a 1 μm finish. [Figure 3B] FIG. 3B shows an SEM image of an article of the invention that was mounted in epoxy, cross-sectioned, and polished to a 1 μm finish. [Figure 4A] FIG. 4A shows the energy dispersive X-ray spectroscopy (EDS) data processing for the ZnI dye penetration test. [Figure 4B] FIG. 4B shows the energy dispersive X-ray spectroscopy (EDS) data processing for the ZnI dye penetration test. [Figure 5A] FIG. 5A shows EDS data for another embodiment of the present invention. [Figure 5B] FIG. 5B shows EDS data for another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present disclosure generally relates to ceramic articles that may be used in a variety of applications, including catalyst support applications, for example, as catalyst supports for catalysts used in the direct oxidation of ethylene to produce ethylene oxide. The ceramic articles described herein include at least a plurality of first alumina particles and a plurality of second alumina particles. The present disclosure also relates to methods of making articles from the first alumina particles and the second alumina particles.

[0010] Without wishing to be bound by any particular theory, it is believed that a ceramic article for making a catalyst support can be provided that solves the problem of how to adjust the amount of active catalyst material loaded on the support, as described herein, thereby providing a more economically competitive catalyst, for example, when a lower catalyst loading on a volumetric basis in the reactor is desired. As described herein, the addition of high density (i.e., low porosity) regions throughout the silver-impregnated catalyst allows the catalyst to simulate a higher work rate than would be possible in an otherwise identical catalyst that does not contain the low porosity regions, thereby allowing a reduction in the amount of silver in the reactor while maintaining the reactor production rate. In some embodiments, such adjustments can simulate a high work rate in a catalyst system, for example, an ethylene oxidation (EO) catalyst system. By introducing large high density / low porosity regions in the support, there will be regions in the support that the active catalyst material cannot infiltrate. However, in the matrix regions surrounding the large high density / low porosity regions, the water absorption to surface area ratio remains preserved, and the expected concentration and particle size of the active catalyst material in the matrix regions is maintained. By maintaining the ratio of water absorption to surface area in the matrix region, the initial catalytic performance is expected to be maintained even if the total loading of active catalytic material on the support is reduced, compared to supports made without large high density / low porosity regions. If the expected life of the catalyst is relatively short, using a smaller amount of active catalytic material, e.g., silver, provides an economic advantage, so that a larger amount of active catalytic material does not provide an advantage over the life of the catalyst. In addition, it is desirable that the shrinkage of the alumina used in the support is suitably adapted to avoid cracking around one or more alumina particles during heat treatment of the support during manufacture. The porosity introduced by any cracks may change the ratio of water absorption to surface area of ​​the matrix phase, which may have the effect of reducing some of the advantages introduced by the present invention.

[0011] One embodiment relates to a ceramic article, the article comprising a continuous matrix including a plurality of first alumina particles and a dispersed phase including a plurality of second alumina particles. The second alumina particles are distributed within the continuous matrix and may be described as a plurality of discrete regions. The dispersed phase has a different ZnI2 dye penetrant test value than the continuous matrix, and in a cross-section of the ceramic article, the dispersed phase occupies between about 8% and about 40% of the cross-sectional area of ​​the ceramic article.

[0012] As used herein, the term "ratio" is defined as a numerical relationship between a first amount of a particular feature (e.g., weight, particle size, atomic percent, surface area, fraction of cross-sectional area, etc.) and a second amount of the same feature. Several illustrative examples are provided below. In the first example, in a mixture of two alumina powders having a total mass of 100 grams and consisting of a first alumina and a second alumina, the amount of the first alumina being 95 grams and the amount of the second alumina being 5 grams, the ratio of the first alumina to the second alumina is 95:5. For convenience, this ratio can be written as 19:1. When the amount of each alumina is expressed as a percentage of the total alumina, the percentage of the first alumina is 95 weight percent and the percentage of the second alumina is 5 weight percent. In the second example, the d of the first alumina is 95 weight percent and the d of the second alumina is 5 weight percent. 50 The particle size is 10 microns, and the second alumina d 50 If the particle size is 150 microns, the ratio is 10:150, which can be simplified to 1:15. This ratio is the d of the second alumina 50 The particle size of the first alumina is d 50 In the third example, the surface area of ​​the first alumina is 5 m 2 / g, and the surface area of ​​the second alumina is 0.5 m 2 / g, the ratio is 5:0.5, which can be written as 10:1. This ratio requires that the surface area of ​​the first alumina is 10 times greater than the surface area of ​​the second alumina. In a fourth example, if the total cross-sectional area of ​​the article is 10 cm 2 and the total cross-sectional area of ​​the item is 8 cm 2 The first powder occupies 2 cm 2If the article consists solely of a first powder and a second powder occupying 10 cm2, then the ratio of the cross-sectional areas occupied by the first and second powders, respectively, is 8:2, which may be written as 4:1. This ratio requires that the cross-sectional area occupied by the first powder is four times greater than the cross-sectional area occupied by the second powder. Expressed as a percentage, the first powder occupies 80 percent of the total cross-sectional area and the second powder occupies 20 percent of the total cross-sectional area. In the fifth example, if the article consists solely of a first powder and a second powder occupying 10 cm2, then the ratio of the cross-sectional areas occupied by the first and second powders, respectively, is 8:2, which may be written as 4:1. This ratio requires that the cross-sectional area occupied by the first powder is four times greater than the cross-sectional area occupied by the second powder. Expressed as a percentage, the first powder occupies 80 percent of the total cross-sectional area and the second powder occupies 20 percent of the total cross-sectional area. 2 and the total cross-sectional area is 5 cm 2 The first powder occupies 5 cm 2 In the sixth example, if the article consists solely of a second powder occupying 20 cm2, the ratio of cross-sectional area occupied by the first and second powders, respectively, is 5:5, which may be described as 1:1. Expressed as a percentage, the first powder occupies 50 percent of the total cross-sectional area and the second powder occupies 50 percent of the total cross-sectional area. ... 2 and the total cross-sectional area is 19.0 cm 2 The first powder occupies 1.0 cm 2 When the alumina particle is composed only of a second powder occupying 95 percent of the total surface area, the ratio of the cross-sectional areas occupied by the first and second powders is 19:1. Expressed as a percentage, the first powder occupies 95 percent of the total surface area and the second powder occupies 5 percent of the total surface area. Thus, in an embodiment in which the ratio of the cross-sectional area of ​​the first alumina particles to the cross-sectional area of ​​the second alumina particles is 1.0:1.0 to 19.0:1.0, the cross-sectional area of ​​the first alumina particles is 50% to 95% of the total cross-sectional area and the cross-sectional area of ​​the second alumina particles is 50% to 5% of the total cross-sectional area.

[0013] One embodiment of the invention described herein is a ceramic article comprising a hard formation of alumina particles comprising a plurality of first alumina particles and a plurality of second alumina particles. Both plurality of particles are randomly distributed throughout the hard formation. The second alumina particles have a ZnI2 dye penetration test value of 5 atomic percent or less, and the first alumina particles have a ZnI2 dye penetration test value at least twice the ZnI2 dye penetration test value of the second alumina particles. Each of the plurality of particles occupies a portion of the total cross-sectional area of ​​the hard formation. The second alumina particles cover about 8% to about 40%, more preferably 10% to 30% of the total cross-sectional area of ​​the ceramic article. A catalytically active metal is dispersed on the first and second alumina particles.

[0014] Another embodiment of the invention described herein is a process for the manufacture of an article comprising a hard formulation of alumina particles and a catalytically active metal in contact with the particles. The process includes the steps of: 50 A plurality of first alpha alumina particles having a particle size are provided. A plurality of second alpha alumina particles having a known weight and selected from the group consisting of fused alumina and platelet alumina are provided. The second alumina particles have a d of about 5 to 400 microns. 50 The first alumina particles have a particle size of d 50 Particle size and d of second alumina particles 50 The ratio of the particle size is 1:4 to 1:40. The ratio of the weight of the first alumina to the weight of the second alumina is 1:1 to 19:1. Mixing a plurality of alumina particles, thereby forming a mixture having the particles randomly distributed throughout the mixture. Forming the mixture into a plurality of malleable articles. Heating the malleable articles to a sintering temperature of the alumina particles, thereby forming each malleable article into a hard formation of alumina particles, the particles in each of the plurality of particles being randomly distributed throughout the hard formation. Depositing a catalytically active metal on the first and second alumina particles.

[0015] As used herein, a continuous matrix refers to a portion of a ceramic article that has morphological characteristics that are relatively unchanged in any direction throughout the article, at least over a distance greater than the longest grain in the dispersed phase. When viewed in cross section through the article, the continuous matrix appears to surround discrete regions of the dispersed phase that appear as individual, separate particles that rarely touch another particle of the dispersed phase. The definition of a continuous matrix applies even though in certain formulations, pores may be included that may introduce gaps in the matrix. With reference to FIG. 2C, region 212 is part of the continuous matrix, region 206 is a discrete region of the dispersed phase, and region 218 is a pore region. This definition applies, and is not negated, by the inappropriate choice of high magnification visual inspection techniques, where at certain magnifications, regions of the matrix may not appear continuous due to a very limited (high magnification) field of view.

[0016] As used herein, the dispersed phase refers to discrete regions that are generally island-like and isolated relative to the enclosing continuous matrix. This definition of the dispersed phase applies even though some dispersed regions may be adjacent, in contact with, or sintered to other dispersed regions (see, for example, FIG. 3A, which shows adjacent discrete regions 302 and 304 of the dispersed phase). In contrast, as shown in FIG. 5A, region 501 is part of a continuous matrix and region 502 is a discrete region in the dispersed phase.

[0017] The dispersed phase coverage of the cross section can be measured at a magnification of 100x to 250x, although any other suitable magnification can be used. In some embodiments, the cross section has a first dimension of about 0.6mm to about 1.5mm and a second dimension of about 0.45mm to about 1mm, in some embodiments, the first dimension can be a length and the second dimension can be a width. In some embodiments, in the cross section of the ceramic article, the majority of the plurality of discrete regions appear to have a longest dimension of about 10μm to about 150μm. Without wishing to be bound by any particular theory, the size can include any size of the discrete regions, such as the Feret diameter (e.g., Henk G. Merkus, Particle Size Measurements: Fundamentals, Practice, Quality; 1 January 2009; Springer, p. 15).

[0018] The penetration test value is determined using the ZnI2 solution penetration test described below. The ZnI2 dye penetration test value of the dispersed phase is lower than the ZnI2 dye penetration test value of the continuous matrix. Generally, the ZnI2 dye penetration test value is obtained by subjecting the ceramic article to a ZnI2 dye penetration test using a ZnI2-containing solution. When the ceramic article is contacted with the ZnI2 solution, for example by submerging the article in the solution, the solution is absorbed into the ceramic article. The solution contains compounds that, once absorbed into the ceramic article, can be identified as absorbed into the article by various analytical methods.

[0019] Generally, the ZnI2 used to determine the penetration test value is dissolved in a suitable solvent, for example, water. One or more samples of ceramic articles are introduced into the resulting ZnI2 solution. Optionally, the solution containing the ceramic material can be subjected to a vacuum, which can ensure better penetration of the solution into the ceramic article. After removing the sample from the solution, drying is used to remove the solvent, leaving the ZnI2 embedded in the ceramic article. The dried sample is mounted by fixing the sample in a polymer or resin material. The sample can be polished, cut, or both, as necessary, to obtain a smooth cross-section of the ceramic article. The ceramic article sample is carbon coated and then analyzed by scanning electron microscopy (SEM) and / or energy dispersive X-ray spectroscopy. By calculating the amount of the penetration test material in the continuous matrix and the dispersed phase, the penetration test value of each region can be calculated.

[0020] In some embodiments, the difference in the permeation test values ​​is at least 5%. In other embodiments, the difference in the permeation test values ​​is at least 5.1%, at least 5.2%, at least 5.3%, at least 5.4%, at least 5.5%, at least 5.6%, at least 5.7%, at least 5.8%, at least 5.9%, at least 6%, at least 6.1%, at least 6.2%, at least 6.3%, at least 6.4%, at least 6.5%, at least 6.6%, at least 6.7%, at least 6.8%, at least 6.9%, at least 7%, at least 7.1%, at least 7.2%, at least 7.3%, at least 7.4%, or at least at least 7.5%, at least 7.6%, at least 7.7%, at least 7.8%, at least 7.9%, at least 8%, at least 8.1%, at least 8.2%, at least 8.3%, at least 8.4%, at least 8.5%, at least 8.6%, at least 8.7%, at least 8.8%, at least 8.9%, at least 9%, at least 9.1%, at least 9.2%, at least 9.3%, at least 9.4%, at least 9.5%, at least 9.6%, at least 9.7%, at least 9.8%, at least 9.9%, or at least 10%.

[0021] In some embodiments, the ZnI2 dye penetration test value of the first alumina is at least three times greater than the Znh dye penetration value of the second alumina.

[0022] In some embodiments, the ZnI2 dye penetration test value of the first alumina is at least four times greater than the ZnI2 dye penetration value of the second alumina.

[0023] In some embodiments, the ratio of the Dye Penetration Test value of the continuous matrix to the Dye Penetration Test value of the dispersed phase is at least 2.0. In other embodiments, the ratio of the Dye Penetration Test value of the continuous matrix to the Dye Penetration Test value of the dispersed phase is at least 2.1, at least 2.2, at least 2.3, at least 2.4, at least 2.5, at least 2.6, at least 2.7, at least 2.8, at least 2.9, at least 3, at least 3.1, at least 3.2, at least 3.3, at least 3.4, at least 3.5, at least 3.6, at least 3.7, at least 3.8, at least 3.9, at least 4, at least 4.1, at least 4.2, at least 4.3, at least 4.4, at least 4.5, at least 4.6, at least 4.7, at least 4.8, at least 4.9, or at least 5.

[0024] In some embodiments, the continuous matrix has a ZnI2 Permeation Test Value of greater than 10%. In other embodiments, the continuous matrix has a ZnI2 Permeation Test Value of at least 10%, at least 11%, at least 12%, at least 13%, at least 14%, at least 15%, at least 16%, at least 17%, at least 18%, at least 19%, at least 20%, at least 21%, at least 22%, at least 23%, at least 24%, at least 25%, at least 26%, at least 27%, at least 28%, at least 29%, at least 30%, at least 31%, at least 32%, at least 33%, at least 34%, at least 35%, at least 36%, at least 37%, at least 38%, at least 39%, at least 40%, at least 41%, at least 42%, at least 43%, at least 44%, at least 45%, at least 46%, at least 47%, at least 48%, at least 49%, or at least 50%.

[0025] In some embodiments, the dispersed phase has a ZnI2 dye penetration test value of 5% or less. In other embodiments, the dispersed phase has a value of less than 1%, less than 1.1%, less than 1.2%, less than 1.3%, less than 1.4%, less than 1.5%, less than 1.6%, less than 1.7%, less than 1.8%, less than 1.9%, less than 2%, less than 2.1%, less than 2.2%, less than 2.3%, less than 2.4%, less than 2.5%, less than 2.6%, less than 2.7%, less than 2.8%, less than 2.9%, less than 3%. ZnI2 dye penetration test value of less than 3.1%, less than 3.2%, less than 3.3%, less than 3.4%, less than 3.5%, less than 3.6%, less than 3.7%, less than 3.8%, less than 3.9%, less than 4%, less than 4.1%, less than 4.2%, less than 4.3%, less than 4.4%, less than 4.5%, less than 4.6%, less than 4.7%, less than 4.8%, or less than 4.9%.

[0026] In some embodiments, the ceramic article is about 0.2 cm 3 / g ~ approx. 0.7cm 3 In some embodiments, the ceramic article has a total pore volume of about 0.3 cm 3 / g ~ approx. 0.6cm 3In some embodiments, the ceramic article has a total pore volume of about 0.35 cm 3 / g ~ approx. 0.5cm 3 The total pore volume, median pore size, and pore size distribution of the support can be measured by conventional mercury intrusion porosimetry equipment, which forces liquid mercury into the pores of the support. More pressure is required to force the mercury into smaller pores, and the measurement of the pressure increment corresponds to the volume increment of the infiltrated pores, and therefore the size of the pores in the incremental volume. The pore size distribution and pore volume of the alumina were measured using a Micromeritics Model 9520 Autopore IV (mercury contact angle of 130°, mercury with a surface tension of 0.480 N / m, and correction for mercury compression applied), starting at 689 Pa and then 4.1×10 7 The pore size can be measured by mercury intrusion porosimetry at increasing pressures up to 100 Pa. A minimum of 100 data points is appropriate. As used herein, median pore size is understood to mean the pore size corresponding to the point in the pore size distribution where 50% of the total pore volume is found in pores smaller (or larger) than that point.

[0027] In another embodiment, the ceramic article is 0.20 cm 3 / g, approx. 0.21cm 3 / g, approx. 0.22cm 3 / g, approx. 0.23cm 3 / g, approx. 0.24cm 3 / g, approx. 0.25cm 3 / g, approx. 0.26cm 3 / g, approx. 0.27cm 3 / g, approx. 0.28cm 3 / g, approx. 0.29cm 3 / g, 0.30cm 3 / g, approx. 0.31cm 3 / g, approx. 0.32cm 3 / g, approx. 0.33cm 3 / g, approx. 0.34cm 3 / g, approx. 0.35cm 3 / g, approx. 0.36cm 3 / g, approx. 0.37cm 3 / g, approx. 0.38cm3 / g, approx. 0.39cm 3 / g, 0.40cm 3 / g, approx. 0.41cm 3 / g, approx. 0.42cm 3 / g, approx. 0.43cm 3 / g, approx. 0.44cm 3 / g, approx. 0.45cm 3 / g, approx. 0.46cm 3 / g, approx. 0.47cm 3 / g, approx. 0.48cm 3 / g, approx. 0.49cm 3 / g, 0.50cm 3 / g, approx. 0.51cm 3 / g, approx. 0.52cm 3 / g, approx. 0.53cm 3 / g, approx. 0.54cm 3 / g, approx. 0.55cm 3 / g, approx. 0.56cm 3 / g, approx. 0.57cm 3 / g, approx. 0.58cm 3 / g, approx. 0.59cm 3 / g, approx. 0.60cm 3 / g, approx. 0.61cm 3 / g, approx. 0.62cm 3 / g, approx. 0.63cm 3 / g, approx. 0.64cm 3 / g, approx. 0.65cm 3 / g, approx. 0.66cm 3 / g, approx. 0.67cm 3 / g, approx. 0.68cm 3 / g, approx. 0.69cm 3 / g, or about 0.70 cm 3 / g pore volume.

[0028] In some embodiments, the ceramic article is about 0.4 mm 2 / g ~ approx. 3m 2 In some embodiments, the ceramic article has a total surface area of ​​about 0.4 m 2 / g ~ approx. 1.5m 2 In some embodiments, the ceramic article has a total surface area of ​​about 0.5 m 2 / g~approx.0.85m 2 / g total surface area.

[0029] Here, the method used to measure the surface area of ​​the ceramic articles is described. A gas sorption analyzer was used to determine the Specific Surface Area (SSA) (also referred to herein as "surface area") of each ceramic article according to the Brunauer-Emmett-Teller (BET) method, which uses liquid nitrogen at 77° K to measure five points. This method can be used to determine the SSA of thermally stable materials having type II or type IV nitrogen sorption isotherms. This procedure follows guidelines set by the International Union of Pure and Applied Chemistry (IUPAC), which are also incorporated into the ASTM and ISO standards referenced below: Thommes, M. et al., Physisorption of gases, with special reference to the evaluation of surface area and pore size distribution (IUPAC Technical Report). Pure Appl. Chem., 87(9-10) (2015), pp. 1051-1069. Stephen Brunauer, PH Emmett, and Edward Teller, Adsorption of Gases in Multimolecular Layers. J. Am. Chem. Soc. 1938, 60, 2, 309-319. ASTM D3663-20 and ASTM C1069-09. ISO 9277:2010.

[0030] Surface area measurements included in this application were performed using a Micromeritics ASAP 2420 or ASAP 2460 using a test tube with a 20cc valve filled to the maximum level. The sample was degassed at 250°C for 2 hours, then cooled and back-filled with nitrogen. The sample tube was then filled into the analysis port and the BET analysis was performed. Surface area was calculated by the BET equation. Calculations were performed using five data points of N2 sorption at relative pressures (P / Po) ranging from 0.05 to 0.30, with the following relative pressure targets: 0.100, 0.125, 0.175, 0.225, and 0.270 P / Po.

[0031] In another embodiment, the ceramic article is about 0.5 mm 2 / g, approx. 0.6m 2 / g, approx. 0.7m 2 / g, approx. 0.8m 2 / g, approx. 0.9m 2 / g, approx. 1m 2 / g, approx. 1.1m 2 / g, approx. 1.2m 2 / g, approx. 1.3m 2 / g, approx. 1.4m 2 / g, approx. 1.5m 2 / g, approx. 1.6m 2 / g, approx. 1.7m 2 / g, approx. 1.8m 2 / g, approx. 1.9m 2 / g, approx. 2m 2 / g, approx. 2.1m 2 / g, approx. 2.2m 2 / g, approx. 2.3m 2 / g, approx. 2.4m 2 / g, approx. 2.5m 2 / g, approx. 2.6m 2 / g, approx. 2.7m 2 / g, approx. 2.8m 2 / g, approx. 2.9m 2 / g, or about 3.0m 2 / g total surface area.

[0032] As used herein, the "water absorption" of the carrier was determined using the following process: Two 100 gram lots of carrier were weighed using an analytical balance. The dry weight of each lot was recorded and the total dry weight (DW) of the combined lots was calculated. Each lot was placed into one of two stainless steel swing buckets, each 80 mm long x 60 mm wide x 70 mm high. The baskets had a diameter of 0.889 mm (0.035 inches) and were constructed from 10 mesh stainless steel screen using wire suitable for use in the Eppendorf Swing Basket Rotor A-4-62 centrifuge available from Eppendorf North America (Hauppauge, New York, USA). The filled wire basket was placed in a vacuum chamber and a vacuum was pulled to 25 mmHg for 2 minutes. Water was poured onto the carrier until it was completely covered. A vacuum was again pulled to 25 mmHg and held for 2 minutes. The vacuum was released and the chamber was returned to atmospheric pressure and left for 2 minutes. The loaded wire basket was placed in an Eppendorf Swing Basket Rotor A-4-62 centrifuge and the loaded basket was spun at 300 revolutions per minute (rpm) for a total spin time of 1 minute. The carriers were emptied from the basket and transferred to a single shallow pan whose weight was previously recorded. The centrifuge weight (CW) of the combined lot was calculated by weighing the pan with the loaded carriers on it and subtracting the weight of the pan. Water absorption was determined by subtracting the dry weight (DW) from the centrifuge weight (CW) to get the difference, which was then divided by the dry weight (DW) and multiplied by 100.

[0033] As used herein, the packed density of a powder is determined as follows: Using a 100 mL graduated cylinder, weigh the graduated cylinder (A) to the nearest 0.01 g, then place it on the platform of the density analyzer with automatic tap and secure it. Add a volume of sample to the capacity of the graduated cylinder. Set the counter for 1000 taps and begin tapping. Once 1000 taps are completed, read and record the volume of the sample (V). The volume should be measured to within 0.5 mL. Weigh the sample and graduated cylinder (B) to the nearest 0.01 g. The tapped packed density can then be calculated as the weight of the powder (BA) divided by the recorded volume V.

[0034] In one embodiment, the ceramic article comprises a continuous alumina matrix and a dispersed alumina phase distributed within the matrix as a plurality of discrete domains, the ceramic article having an area of ​​less than 0.3 cm 3 / g~0.6cm 3 / g and a total pore volume of 0.5 cm 2 / g~0.85cm 2 / g, wherein a majority of the plurality of discrete regions each have a size of from about 10 μm to about 150 μm, the continuous alumina matrix has a ZnI2 dye penetrant test value of 10% or greater, and the dispersed alumina phase has a ZnI2 dye penetrant test value of 5% or less, and in a cross-section of the ceramic article having a first dimension of from about 0.6 mm to about 1.5 mm and a second dimension of from about 0.45 mm to about 1 mm, the dispersed alumina phase occupies from 5% to 50%, more preferably from 8% to 40%, and even more preferably from 10% to 30% of the cross-sectional area.

[0035] The present disclosure also relates to a catalyst comprising a metal deposited on the ceramic article described herein. One embodiment relates to a catalyst in which the metal is silver deposited on the ceramic article described herein. The present disclosure relates to a method of adjusting the amount of metal loaded on the article by varying the ratio between the amount of the first alumina powder and the amount of the second alumina powder used to make the support. Because the dispersed phase is less porous than the continuous matrix (as reflected in the dispersed phase's lower ZnI2 penetration test value), the dispersed phase has a lower metal catalyst loading than the continuous matrix. Thus, by increasing the ratio of the dispersed phase to the continuous matrix in the ceramic article, the metal catalyst loading can be reduced, and conversely, by decreasing the ratio of the dispersed phase to the continuous matrix in the ceramic article, the metal catalyst loading can be increased.

[0036] To produce the articles of the present invention, certain physical and chemical properties, specifically the surface area and d 50 Particle size can be controlled and tailored. Powders useful in making the articles of the invention can be selected using the information in Table 1 and the following description as a guide.

[0037] [Table 1] Preferably, the first alumina powder has a d of 0.2 to 100 microns, more preferably 2 to 20 microns, and most preferably 5 to 10 microns. 50 The first alumina powder has a maximum firing temperature of about 1600°C and a surface area of ​​1 to 20 m 2 / g, preferably 1 to 5m 2 / g, more preferably 1 to 2m 2 / g. The first alumina powder may include internal porosity that contributes significantly to its total surface area, which is a measure of the surface area contributed by the internal porosity and geometric surface area of ​​the particle. The first alumina powder should not be fused alumina or platelet alumina. As used herein, platelet alumina is defined as aluminum oxide heated to a temperature above 1,650°C and composed of tablet-like crystals. As used herein, fused alumina is defined as calcined alumina that has been melted in an electric arc furnace, cooled, crushed, and recast into the desired shape. Calcined alumina is aluminum oxide that has been heated to a temperature above 1,050°C to remove nearly all chemically bound water.

[0038] Preferably, the second alumina is an alpha alumina selected from the group consisting of platelet alumina and fused alumina. The second alumina powder is an alpha alumina made in a process in which the maximum firing temperature may be higher than the melting point of the alumina, as in the case of fused alumina, or slightly lower than the melting point of the alumina, as in the case of platelet alumina. The d of the second alumina 50 The particle size may be 5-400 microns, more preferably 10-200 microns, and most preferably 40-150 microns. Because the second alumina powder has been calcined near or above the melting point of alumina, the second alumina powder has very little internal porosity. The lack of internal porosity results in a lower total surface area than the first alumina powder of similar particle size, since there is no internal porosity to contribute to the total surface area. The second alumina powder, which has not been subjected to a grinding process to reduce the particle size, has a particle size of 0.2-2.0 m. 2 / g, preferably 0.10 to 0.50 m 2 / g, more preferably 0.14 to 0.30 m 2 / g surface area.

[0039] d of the second alumina 50 d of the first alumina versus particle size 50Selecting the ratio of particle sizes can be used to control the total surface area of ​​the article made from the first and second alumina powders. As a general rule, the particle size of the first alumina powder should be much smaller than the particle size of the second alumina powder. Preferably, the d of the first alumina 90 is the d of the second alumina 10 More preferably, the d of the first alumina should be less than 95 is the d of the second alumina 05 Even more preferably, the d of the first alumina should be less than 1. 99 is the d of the second alumina 01 Preferably, the particle size distribution of the first and second aluminas should be monomodal.

[0040] More specifically, the d of the first alumina powder 50 Particle size vs. d of the second alumina powder 50 The particle size ratio may be 1:4 to 1:40, preferably 1:5 to 1:20, more preferably 1:8 to 1:15. These ratios are determined by the d of the second alumina powder. 50 The particle size of the first alumina powder is d 50 It is shown that the d of the second alumina powder should be 40 times or less, preferably 20 times or less, and more preferably 15 times or less than the particle size. This ratio also indicates that the d 50 The particle size of the first alumina powder is d 50 This indicates that the particle size must be at least 4 times, preferably at least 5 times, and more preferably at least 8 times larger than the particle size.

[0041] Absolute d of the first and second alumina powders 50In addition to particle size and their ratio, the surface area of ​​the first alumina and the second alumina powder can be used to select powders useful for making the article of the present invention. As a general rule, the surface area per gram of the first alumina powder should be much greater than the surface area per gram of the second alumina powder. More specifically, the ratio of the surface area of ​​the first alumina powder to the surface area of ​​the second alumina powder can be 7:1 to 15:1, preferably 5:1 to 10:1, more preferably 4:1 to 5:1. These ratios indicate that the surface area of ​​the first alumina powder should be 15 times or less, preferably 10 times or less, more preferably 5 times or less than the surface area of ​​the second alumina powder. This ratio also indicates that the surface area of ​​the first alumina powder should be at least 7 times, preferably at least 5 times, more preferably at least 4 times greater than the surface area of ​​the second alumina powder.

[0042] The second alumina particles are sometimes referred to herein as the dispersed phase and are randomly distributed throughout the continuous matrix phase. The second alumina particles are considered not to form a continuous phase if at least 70% of the second alumina particles visible in a SEM micrograph of the article of the present invention at a desired magnification do not appear to be in contact with other second alumina particles. The second alumina particles may appear to be physically separated from other second alumina particles by a plurality of first alumina particles that completely or partially surround the second alumina particles.

[0043] Alumina type, specific d 50 In addition to the particle sizes and their ratios, the weight ratio of the first and second powders can be controlled to ensure that the cross-sectional area of ​​the second alumina particles is at least 5-50%, more preferably 8%-40%, and even more preferably 10%-30% of the total cross-sectional area of ​​the article. The weight ratio of the first alumina powder to the second alumina powder can be 15:1 to 1:1. Intermediate ratios of 14:1, 12:1, 10:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, and 2:1 are feasible.

[0044] One embodiment relates to a method for making a ceramic article, wherein the first alumina powder can be at least 85 weight percent alpha-alumina. More preferably, the first alumina powder can be at least 90 weight percent, 95 weight percent, or 99 weight percent alpha-alumina. One embodiment relates to a method for making a ceramic article, wherein the second alumina powder can be only fused alumina, only tabular alumina, or a mixture of tabular alumina and fused alumina.

[0045] As described herein, particle size is determined by laser scattering using a Horiba Particle LA-950 Laser Scattering Particle Size Distribution Analyzer. The analyzer uses the principles of Mie scattering theory to measure particle size and distribution in the range of 0.01 microns to 3000 microns. 50 The median particle size, referred to as "particle diameter," represents the particle size at which the spherical equivalent volume of particles larger than and smaller than the stated median particle size is equal. The method involves adding three drops of a 10% Darvan® solution and dispersing the particles by ultrasonic treatment, thus breaking down the secondary particles into primary particles. This ultrasonic treatment is called d 50 It is continued until no further change in value is observed, which typically requires 1-5 minutes of sonication when using a Horiba LA-950 particle size analyzer.

[0046] In some embodiments, the method for making the ceramic article includes the use of a binding material, such as magnesium silicate. If desired, one or more optional additives can be included in preparing the ceramic article. For example, it may be desirable to include one or more additives to facilitate formation of the compact and / or to alter one or more properties of the resulting ceramic article. Suitable additives may include any of a wide variety of known carrier additives, including, but not limited to, binders (e.g., polyolefin oxides, cellulose, alkaline earth metal compounds such as magnesium silicate and calcium silicate, and alkali metal compounds), extrusion aids (e.g., petrolatum, hydrogenated oils, synthetic alcohols, synthetic esters, glycols, starches, polyolefin oxides, polyethylene glycols, and mixtures thereof), solvents (e.g., water), deflocculating acids (e.g., monofunctional aliphatic carboxylic acids containing 1 to about 5 carbon atoms, such as formic acid, acetic acid, and / or propanoic acid), halogenated monofunctional aliphatic carboxylic acids containing 1 to about 5 carbon atoms (e.g., mono-, di-, and trichloroacetic acid, etc.), fluxes, binders, dispersants, burn-off materials also known as "pore formers," strength-enhancing additives, and the like. For example, it is within the ability of one of ordinary skill in the art to select suitable additives in appropriate amounts, taking into account the preparation method and desired properties of the resulting ceramic article.

[0047] In some embodiments, the process includes the use of formic acid. Formic acid can function to stabilize the dispersion of particles in the mixture. In some embodiments, formic acid is added to the mixture at about 1% (w / w%), about 1.5% (w / w%), about 2% (w / w%), about 2.5% (w / w%), about 3% (w / w%), about 3.5% (w / w%), about 4% (w / w%), about 4.5% (w / w%), about 5% (w / w%), about 5.5% (w / w%), about 6% (w / w%), about 6.5% (w / w%), about 7% (w / w%), or about 7.5% (w / w%).

[0048] In some embodiments, the mixture further comprises one or more pyrolyzable materials. The mixture may contain the pyrolyzable material in an amount ranging from about 2% (w / w%) to about 40% (w / w%), or from about 5% (w / w%) to about 30% (w / w%). The pyrolyzable material may function as a pore former. As used herein, the pyrolyzable material is a solid in particulate form. The pyrolyzable material is mixed with alumina powder, e.g., a green mixture of at least two different types of alumina, prior to the heating step. The individual particles of the pyrolyzable material occupy many small spaces in the mixture. The individual particles of the pyrolyzable material are removed by pyrolysis during the heating step and / or sintering step, thereby leaving pores in the ceramic article forming the carrier. The pores may also be described as a plurality of voids distributed throughout the ceramic article. In some embodiments, the majority of the pores created by the use of the pyrolyzable material are contained within a continuous matrix. For example, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the pores created through the use of pyrolyzable materials are contained within a continuous matrix.

[0049] The pyrolyzable material should not be soluble in any of the other components used to make the ceramic article. Similarly, the pyrolyzable material should not dissolve any of the other components. The pyrolyzable material occupies a volume prior to the heating step, and the space occupied by the material remains generally unoccupied after the heating step is completed, so that the material functions as a pore former. The pyrolyzable material useful in the process of the present invention is typically an organic material. Suitably, the chemical formula of the organic material includes carbon and hydrogen. The pyrolyzable material may be a synthetic or natural material or a mixture thereof. Preferably, the pyrolyzable material may be an organic material having a decomposition temperature below the sintering temperature of the alumina powder. This ensures that the pyrolyzable material is at least partially removed before or simultaneously with the sintering of the alumina powder. To facilitate decomposition, the chemical formula of the pyrolyzable material may preferably include carbon, hydrogen, and oxygen. The decomposition temperature may be reduced by the presence of oxygen.

[0050] In some embodiments, the mixture further comprises one or more naturally occurring pyrolyzable materials that result in the formation of pores during burnout. As used herein, naturally occurring pyrolyzable materials do not include polymers in the formulation and do not include other processing aids. Rather, naturally occurring pyrolyzable materials refer to burnout materials that are optionally included when preparing ceramic articles to facilitate the shaping of the compact and / or to alter the porosity of the resulting ceramic article. Typically, the burnout materials are burned out, sublimated, or volatilized during drying, firing, and / or sintering. Examples of suitable burnout materials include, but are not limited to, ground shells of nuts such as pecan, cashew, walnut, peach, apricot, and filbert. Any other naturally occurring pyrolyzable materials known in the art can be used. In some embodiments, the pore volume of 0.1 mL / g or less in the resulting ceramic article is due to the use of a burnout material. In some embodiments, naturally occurring pyrolyzable materials are not included in the mixture.

[0051] The thermally decomposable material may be a synthetic material. The synthetic material may be a polymeric material. Without wishing to be bound by any particular theory, it is contemplated that synthetic materials, as used herein, do not include naturally occurring thermally decomposable materials. The polymeric material may be formed using emulsion polymerization, including suspension polymerization, which is often preferred since it results in particulate polymers that can be directly used as thermally decomposable materials. Preferably, the polymeric material may be formed using anionic polymerization. The polymeric material may be olefin polymers and copolymers, such as polyethylene, polypropylene, polystyrene, polyvinyl alcohol, ethylene-vinyl acetate, and ethylene-vinyl alcohol copolymers, diene polymers and copolymers, such as polybutadiene, EPDM rubber, styrene-butadiene copolymers, and butadiene-acrylonitrile rubber, polyamides, such as polyamide-6 and polyamide-66, polyesters, such as polyethylene terephthalate. Preferably, the polymeric material may be a hydrocarbon polymer, such as a polyolefin, more preferably polypropylene.

[0052] The pyrolyzable material may be screened or otherwise selected to limit the size of the individual particles to a particular particle size range. If desired, a first pyrolyzable material having particles within a first particle size range may be combined with a second pyrolyzable material having particles within a second particle size range to obtain a multimodal distribution of pore sizes in the porous ceramic article. The particle size range limit is determined by the size of the pores formed in the porous ceramic article of the carrier.

[0053] In some embodiments, the mixture further comprises one or more polymers or copolymers selected from hydroxypropyl methylcellulose, vinyl chloride copolymers, vinyl acetate copolymers, olefin polymers, olefin copolymers, polyethylene, polypropylene, polystyrene, polyvinyl alcohol, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, diene polymers, diene copolymers, polybutadiene, ethylene propylene diene monomer (EPDM) rubber, styrene-butadiene copolymers, butadiene acrylonitrile rubber, polyamide, polyamide-6, polyamide-66, polyester, polyethylene terephthalate, hydrocarbon polymers, polyolefins, and polypropylene. The one or more polymers or copolymers may function as a lubricant and / or a pore former.

[0054] The carrier body may be formed from the mixture by any convenient forming process, such as spray drying, agglomeration, or pressing, and is preferably formed by extrusion of the mixture. For applicable methods, reference may be made, for example, to U.S. Pat. Nos. 5,145,824, 5,512,530, 5,384,302, 5,100,859, and 5,733,842, each of which is incorporated herein by reference. To facilitate such forming processes, particularly extrusion, the mixture may be suitably compounded with 2-25% w / w, preferably 5-15% w / w, of a processing aid. Processing aids, also referred to by the term "extrusion aids", are known in the art, for example, as described in "Kirk-Othmer Encyclopedia of Chemical Technology," 4th edition, Volume 5, p.610. Suitable processing aids are typically liquid or greasy substances such as petrolatum, hydrogenated oils, synthetic alcohols, synthetic esters, glycols, or polyolefin oxides. Boric acid may also be added to the mixture, for example, in amounts up to 0.5% w / w%, more typically 0.01-0.5% w / w%. All formulation weights are based on the total weight of the ceramics, such as alumina and zirconia, in the mixture.

[0055] In some embodiments, the process further comprises extruding the mixture before calcining and / or sintering. In some embodiments, the process further comprises forming the mixture into one or more individual bodies before calcining and / or sintering. For example, the mixture may be formed into a support. Generally, the size of the supports is determined by the dimensions of the reactor in which they are deposited. However, generally, it has been found very convenient to use supports in the form of cylinders, spheres, donuts, etc. The cylinders may be solid or hollow, straight or bent, and they may have a length of 4 to 20 mm, typically 5 to 15 mm, an outer diameter of 4 to 20 mm, typically 5 to 15 mm, and an inner diameter of 0.1 to 6 mm, typically 0.2 to 4 mm. The cylinders may have a length to outer diameter ratio in the range of 0.5 to 2, typically 0.8 to 1.2.

[0056] The formed parts can be produced in a variety of shapes, such as cylindrical, spherical, annular, or multi-lobed. For example, shaped pellets can be formed by extruding a continuous rod of paste and then cutting the rod into pellets of the desired size. By extruding the paste through a suitably shaped die and then cutting the rod into pellets of constant cross section, ring-based shaped structures of any desired configuration, such as "wagon wheels", or any other extruded shape with a constant cross section, such as multi-lobed structures and small honeycombs, can be formed. The shaped articles can also be in the form of large honeycomb monoliths. However, the extrusion / pressing process is not limited to these shapes. The parts can have an outer diameter of about 0.8 to about 25 mm, or an average width if non-circular, although other sizes can be formed. Reference can be made to U.S. Patent Application Publication No. 2012 / 0171407, which is incorporated herein by reference for further description of multi-lobed carriers. Additionally, the size of the ceramic article carrier is generally not limited and can include any size suitable for use in catalytic reactors, such as ethylene oxidation reactors. For example, the ceramic article carrier may be cylindrical in shape having a length of 5-15 millimeters, an outer diameter of 5-15 mm, and an inner diameter of 0.2-4 mm, in some embodiments, the ceramic article carrier may have a length to outer diameter ratio of 0.8-1.2. Additionally, the ceramic article carrier may be in the shape of a hollow cylinder having a wall thickness of 1-7 mm, for example, it is within the ability of one of ordinary skill in the art having the benefit of this disclosure to select a suitable shape and size of the ceramic article carrier, taking into account the type and configuration of the catalytic reactor in which the ceramic article carrier will be used, e.g., the length and inner diameter of the tubes in the catalytic reactor.

[0057] In some embodiments, the process further comprises drying the compact. The formed compact may be dried to remove at least a portion of the water present, if any. Water may be converted to steam during the heating step described below and may adversely affect the physical integrity of the compact. Drying may be performed after preparation of the mixture and optional forming of the mixture into a plurality of compacts. The drying step may be combined with the heating step by controlling the thermal profile of the oven or kiln. Drying may be performed at 20°C to 400°C, or 30°C to 300°C, typically for a period of up to about 100 hours, preferably from about 5 minutes to about 50 hours. Typically, drying is performed to the extent that the mixture contains less than 2% w / w water.

[0058] The calcination and / or sintering is generally carried out at a sufficiently high temperature and for a sufficiently long time, up to about 100 hours, preferably from about 5 minutes to about 50 hours. In some embodiments, the calcination and / or sintering may be carried out at one or more temperatures, one or more pressures, and one or more time periods sufficient to sinter at least 50%, or at least 75%, or at least 85%, or at least 90%, or at least 95% of the mixture of at least two aluminas. In some embodiments, the process includes heating the mixture at a temperature of at least 1200° C. In some embodiments, the process includes heating the mixture at a temperature up to 1600° C. In some embodiments, the process includes heating the mixture at a temperature of about 1200° C. to about 1600° C. The calcination and / or sintering may be carried out in any suitable atmosphere, including, but not limited to, air, nitrogen, argon, helium, carbon dioxide, water vapor, and the like. In embodiments where the compact further comprises an organic burnout material, at least one of the heating and / or firing is at least partially or completely performed in an oxidizing atmosphere, such as in an oxygen-containing atmosphere. As used herein, firing and / or sintering refers to the process of firing and solidifying a green body made and formed from powder particles. The particles bond to adjacent particles to form a solid formation of alumina particles. Voids may exist between and / or within the particles, collectively contributing to the porosity of the ceramic article.

[0059] After calcination and / or sintering, the resulting ceramic article may be optionally washed and / or treated prior to deposition of the active catalyst material. Similarly, if desired, any raw materials used to form the ceramic article may be washed and / or treated prior to calcination and / or sintering. Any method known in the art for washing and / or treating may be used in accordance with the present disclosure, so long as such method does not adversely affect the performance of the resulting support or catalyst. For descriptions of such methods, see U.S. Pat. Nos. 6,368,998, 7,232,918, 7,741,499, and WO 2007 / 092022, each of which is incorporated herein by reference. If washing is desired, washing is typically performed at a temperature ranging from 15° C. to 120° C. for a period of up to about 100 hours, preferably from about 5 minutes to about 50 hours. Washing may be performed either continuously or batchwise. Examples of suitable cleaning solutions include, but are not limited to, water, e.g., deionized water, aqueous solutions containing one or more salts, e.g., ammonium salts, amine solutions, e.g., ethylenediamine, aqueous organic diluents, and combinations thereof. Similarly, suitable aqueous solutions may be acidic, basic, or neutral. The volume of the cleaning solution may be such that the ceramic article is impregnated until the point of incipient wetness of the ceramic article is reached. Alternatively, a larger volume may be used and the excess of solution may be removed from the wet ceramic article, e.g., by centrifugation. Additionally, following any cleaning and / or treatment steps, it may be preferable to dry or roast the ceramic article prior to deposition of the catalyst article. For example, the ceramic article may be dried in a stream of air, e.g., at a temperature of about 80°C to about 400°C, for a sufficient time.

[0060] The formed ceramic article can be used directly as a catalyst or can be used as a catalyst support after impregnation with a solution of a catalytically active material during or after formation of the body, and optionally activation by suitable post-treatment. Suitable catalytically active materials include transition metal elements, such as those from groups VB, VIIIB, and IB of the periodic table of the elements, such as vanadium, gold, platinum group metals, and the like. In some embodiments, the metal is a catalytically active metal, including, for example, silver, cobalt, ruthenium, and / or iron. In particular, silver is a preferred metal. An exemplary application in which the support can be used includes direct ethylene oxidation, although it is contemplated that the ceramic article can be used in any application. EXAMPLES

[0061] The process of preparing carriers for use in epoxidation reactions is described in numerous publications, including U.S. Pat. Nos. 5,100,859 and 6,831,037, which are incorporated herein by reference. See, for example, the disclosure in U.S. Pat. No. 5,100,859, column 2, line 6 to column 6, line 43. The following examples further describe some embodiments of the present invention. These examples are provided for illustrative purposes only and should not be considered as limiting the present invention. Carrier A is a comparative example. Carriers B, C, D, and E are embodiments of the present invention described herein.

[0062] Carrier A (Comparative Example) The comparative support in this disclosure, Support A, was prepared according to the teachings of U.S. Pat. No. 5,100,859 (Gerdes) for Support L, with the following modifications. The only alumina powder used in Comparative Support A was a 7.7 micron d 50 Particle size, 1.4m 2The first plurality of alumina particles had a surface area of ​​0.01 g / g and a packing density of 0.78 g / cc, referred to herein as the first plurality of alumina particles. The first plurality of alumina particles was combined with zirconia, magnesium silicate, walnut shell flour, boric acid, and an extrusion aid. The combination of the first plurality of alumina particles, zirconia, magnesium silicate, and walnut shell flour is defined herein as a dry mixture of Carrier A. The combined weight of the dry mixture with water, boric acid, and extrusion aid is defined herein as a wet mixture of Carrier A, which was extruded to form a hollow cylinder that was dried and fired. In Carrier A, the first plurality of alumina particles formed a single continuous matrix phase throughout the carrier. Carrier A did not contain a dispersed phase. The physical and chemical properties of the fired cylinder, which may be referred to as a ceramic article, carrier, or support, were determined using the analytical techniques described above. Carrier A had a water absorption of 48.7 g / g and a surface area of ​​0.78 m 2 It was.

[0063] Carrier B (one embodiment of the present invention) One embodiment of the present invention, Carrier B, was made by following the process used to make Comparative Carrier A described immediately above, except that 10 weight percent of the dry mixture of Carrier A was replaced with an equal mass of a plurality of fused alumina particles, referred to herein as a second plurality of alumina particles, thereby forming the dry mixture of Carrier B. The second plurality of alumina particles had a d 50 , 0.2m 2 Carrier B had a surface area of ​​46.70 g / g and a packing density of 2.1 g / cc. The dry mixture of Carrier B was combined with water, boric acid, and an extrusion aid to make a wet mixture of Carrier B, which was then extruded to form a hollow cylinder, which was dried and calcined. The physical and chemical properties of the calcined cylinder were measured. Carrier B had a water absorption of 46.70 g / g and a surface area of ​​0.74 m. 2 It was.

[0064] Carrier C (one embodiment of the present invention) One embodiment of the present invention, Support C, was made by following the process used to make Support A described above, except that 25 weight percent of the dry mixture of Support A was replaced with an equal mass of a plurality of fused alumina particles, referred to herein as a second plurality of alumina particles, thereby forming the dry mixture of Support C. The second plurality of alumina particles had a d 50 , 0.2m 2 Carrier C had a surface area of ​​0.63 m / g, and a packing density of 2.1 g / cc. The dry mixture of Carrier C was combined with water, boric acid, and an extrusion aid to make a wet mixture of Carrier C, which was then extruded to form a hollow cylinder, which was dried and calcined. The physical and chemical properties of the calcined cylinder were measured. Carrier C had a water absorption of 42.86 g / g, a surface area of ​​0.63 m 2 It was.

[0065] Carrier D (one embodiment of the present invention) One embodiment of the present invention, Carrier D, was made by following the process used to make Carrier A described above, except that 40 weight percent of the dry mixture of Carrier A was replaced with an equal mass of a plurality of fused alumina particles, referred to herein as a second plurality of alumina particles, thereby forming the dry mixture of Carrier D. The second plurality of alumina particles had a d 50 , 0.2m 2 Carrier D had a surface area of ​​0.53 m / g, and a packing density of 2.1 g / cc. A dry mixture of Carrier D was combined with water, boric acid, and an extrusion aid to make a wet mixture of Carrier D, which was then extruded to form a hollow cylinder, which was dried and calcined. The physical and chemical properties of the calcined cylinder were measured. Carrier D had a water absorption of 37.70 g / g, a surface area of ​​0.53 m 2 It was.

[0066] Carrier E (one embodiment of the present invention) One embodiment of the present invention, Carrier E, was made by following the process used to make Carrier A described above, except that 50 weight percent of the dry mixture of Carrier A was replaced with an equal mass of a plurality of fused alumina particles, referred to herein as a second plurality of alumina particles, thereby forming the dry mixture of Carrier E. The second plurality of alumina particles had a d 50 , 0.2m 2 Carrier E had a surface area of ​​0.43 m / g, and a packing density of 2.1 g / cc. The dry mixture of Carrier E was combined with water, boric acid, and an extrusion aid to make a wet mixture of Carrier E, which was then extruded to form a hollow cylinder, which was dried and calcined. The physical and chemical properties of the calcined cylinder were measured. Carrier E had a water absorption of 35.64 g / g, a surface area of ​​0.43 m 2 It was.

[0067] 1 shows that the surface area and water absorption of the support depend on the amount of dispersed phase alumina in the support. Curve 101 shows the relationship between the surface area of ​​the support and the weight percent of the dispersed phase calculated as a percentage of the dry mix of support A. Curve 102 shows the relationship between the water absorption of the support and the weight percent of the dispersed phase calculated as a percentage of the dry mix of support A.

[0068] 2A-2C show the microstructure of a ceramic article of the present invention. Back-scattered electron (BSE) microscopy images show a second alumina powder phase (regions 202, 204, and 206 in FIGS. 2A, 2B, and 2C, respectively) distributed in the first alumina powder (regions 208, 210, and 212 in FIGS. 2A, 2B, and 2C, respectively). The grain size of the second alumina powder is significantly larger than that of the first alumina powder. The magnification of FIG. 2A is 100×. The magnification of FIG. 2B is 250×. The magnification of FIG. 2C is 500×.

[0069] Figures 3A and 3B show the identification of dispersed phase particles in a polished cross section of a ceramic article that was epoxy mounted and polished to a 1 micron finish. The specimen was gold coated to prevent charging using an SPI sputter coater. Images were generated using a Zeiss Merlin SEM using an accelerating voltage of 2 keV and a beam current of 100 pA. The type of SEM used is not critical, but must be capable of generating images suitable for image analysis software to identify and isolate the dispersed phase. SEM images were acquired at 100x magnification for the larger size diluent particles (see Figure 3A) and 250x magnification for the smaller size diluent particles to obtain a particle count of ≥ 100 in each image. Image analysis software was used to identify, isolate, and separate the dispersed phase particles. See Figure 3B. Analysis was performed to determine the total area coverage of the dispersed phase in each image, as well as the Feret mean particle size of each image using imageJ software, an open source image processing program developed at the National Institutes of Health and the Laboratory for Optical and Computational Instrumentation and available for download at imageJ.net. The type of image analysis software used is not critical and one of ordinary skill in the art would be familiar with the image manipulations required to identify and isolate the dispersed phase. The area coverage of the dispersed phase was determined for four images from Carrier E and one image from Carrier C. The area coverage of the dispersed phase from these images was determined to be in the range of 9-23%. The data in Table 2 show that the area coverage of Carrier C was 9.1 percent and the area coverage of the four images of Carrier E was approximately 20 percent.

[0070] [Table 2] ZnI2 dye penetration test values ​​were determined using the following ZnI2 solution penetration test. First, 220 g of ZnI2 was placed in 1,000 mL of water at 20°C, thereby forming a ZnI2 solution. 5 g of a sample of the ceramic article was introduced into the 100 mL of ZnI2 solution. The container holding the sample of the ceramic article in solution was placed in a container under vacuum for 20 hours. The sample was removed from the solution and dried at 50°C for 24 hours and then at 110°C for a minimum of 2 hours. The dried sample was mounted in epoxy resin within 30 minutes of removal from the drying oven to avoid re-absorption of water. After the epoxy cured, the sample was polished to a 3 micron finish and kept in a drying oven at 100°C.

[0071] An SEM manufactured by Hitachi, model S4300, and an EDS detector manufactured by Oxford Instruments, system model Aztec SEM using an X-MaxN 150 detector, and Aztec version 3.3 SP1 software, were used to characterize the distribution of iodide on the alumina particles. Polished samples were carbon coated to prevent charging. SEM-EDS images were taken within the parameters shown in Table 3.

[0072] [Table 3] EDS data was collected using manually selected areas including at least one of the second alumina particles and an equivalent area of ​​the first alumina particle. The EDS software could then generate iodine and zinc concentrations in each area. Both iodine and zinc concentrations could be used to compare the amount of penetration, but iodine was preferred.

[0073] The area of ​​a second alumina particle, one particle in the dispersed phase, is outlined as region 402 in FIG. 4A. EDS was used to determine the amount of iodine in region 402. FIG. 4B is an EDS image showing the location of ZnI2 in FIG. 4A. The dark areas in FIG. 4B indicate the absence of ZnI2, and the light areas indicate the presence of ZnI2. The amount of iodine in a corresponding area of ​​the matrix phase, identified as region 401 in FIG. 4A, was also determined. The amount of iodine recovered in each phase represents the amount of iodide infiltration in a given phase. Table 4 shows analytical data from two different examples of support D. In Table 4, the amount of iodine in the dispersed phase was 0.43 atomic percent, while the amount of iodide in the matrix phase was 14.68 atomic percent. The amount of iodine present in the dispersed phase is much less than the amount of iodine in the matrix phase and is believed to correlate with the amount of catalytically active metal, such as silver, deposited on the same alumina particles when the ceramic article of the present invention is manufactured for use as a catalyst support.

[0074] [Table 4]

[0075] In Table 4, percentages refer to atomic weight percent.

[0076] Fused alumina particles are not infiltrated by ZnI2. SEM images show apparently larger, impenetrable particles distributed throughout the continuous matrix, as shown in FIG. 5A. See particles 502, 504, and 506. FIG. 5B is an EDS image showing the location of ZnI2 in FIG. 5A. The dark areas in FIG. 5B indicate the absence of ZnI2, and the light areas indicate the presence of ZnI2. ZnI2 dye penetration testing demonstrates the ability to create an impermeable phase distributed in the matrix phase.

[0077] Embodiment Embodiment 1. A ceramic article comprising: (a) a hard formation of alumina particles comprising a plurality of first alumina particles and a plurality of second alumina particles, the particles of both plurality being randomly distributed throughout the hard formation; 1) the second alumina particles have a ZnI2 dye penetration test value of 5 atomic percent or less, and the first alumina particles have a ZnI2 dye penetration test value that is at least two times the ZnI2 dye penetration test value of the second alumina particles; 2) the hard formation has a total cross-sectional area, each of the plurality of particles occupying a portion of the total cross-sectional area, the cross-sectional area of ​​the second alumina particles being between 5% and 50% of the total cross-sectional area; (b) a catalytically active metal dispersed on said first and second alumina particles.

[0078] Embodiment 2. The article of embodiment 1, wherein the first alumina has a ZnI2 dye penetration test value that is at least three times greater than the ZnI2 dye penetration test value of the second alumina.

[0079] Embodiment 3. The article of embodiment 1, wherein the first alumina has a ZnI2 dye penetration test value that is at least four times greater than the ZnI2 dye penetration test value of the second alumina.

[0080] Embodiment 4. The article of embodiment 1, wherein the first alumina has a ZnI2 dye penetrant test value of greater than 10 atomic percent.

[0081] Embodiment 5. The article of embodiment 1, wherein the first alumina has a ZnI2 dye penetrant test value of greater than 15 atomic percent.

[0082] Embodiment 6. The article of embodiment 1, wherein the second alumina has a dye penetrant test value of 3 atomic percent or less.

[0083] Embodiment 7. The article of embodiment 1, wherein the ratio of a dye penetrant test value of the first alumina to a dye penetrant test value of the second alumina is at least 2:1.

[0084] Embodiment 8. The article of embodiment 1, wherein the cross-sectional area of ​​the second alumina particles is between 8% and 40% of the total cross-sectional area.

[0085] Embodiment 9. The article of embodiment 1, wherein the cross-sectional area of ​​the second alumina particles is 10%-30% of the total cross-sectional area.

[0086] Embodiment 10. The article of embodiment 1, further comprising a total pore volume of about 0.2 cm3 / g to about 0.6 cm3 / g.

[0087] Embodiment 11. The article of embodiment 10, wherein the total pore volume is from about 0.3 cm3 / g to about 0.5 cm3 / g.

[0088] Embodiment 12. The article of embodiment 10, wherein the total pore volume is from about 0.35 cm3 / g to about 0.5 cm3 / g.

[0089] Embodiment 13. The article of embodiment 1, wherein the catalytically active metal is selected from the group consisting of silver, platinum, palladium, nickel, and copper.

[0090] Embodiment 14. A process for the manufacture of a ceramic article comprising a hard formation of alumina particles and a catalytically active metal in contact with said particles, the process comprising: (a) providing a first plurality of alpha alumina particles having a known weight and a d50 particle size between about 0.2 and 100 microns; (b) providing a plurality of second alpha alumina particles having a known weight and selected from the group consisting of fused alumina and platelet alumina, the second alumina particles having a d50 particle size of about 5-400 microns, a ratio of the d50 particle size of the first alumina particles to the d50 particle size of the second alumina particles being between 1:4 and 1:40, and a ratio of the weight of the first alumina to the weight of the second alumina being between 1:1 and 15:1; (c) mixing the plurality of alumina particles, thereby forming a mixture, wherein the particles are randomly distributed throughout the mixture; and (d) forming the mixture into a plurality of malleable articles; (e) heating the malleable article to a sintering temperature of the alumina particles, thereby forming each malleable article into a hard formation of alumina particles, the particles in each plurality of particles being randomly distributed throughout the hard formation; (f) depositing a catalytically active metal on said first and second alumina particles.

[0091] Embodiment 15. The process of embodiment 14, wherein the ratio of the weight of the first alumina to the weight of the second alumina is from 1:1 to 10:1.

[0092] Embodiment 16. The process of embodiment 14, wherein the ratio of the weight of the first alumina to the weight of the second alumina is from 1:1 to 5:1.

[0093] Embodiment 17. The process of embodiment 14, wherein the ratio of the d50 particle size of the first alumina particles to the d50 particle size of the second alumina particles is from 1:5 to 1:20.

[0094] Embodiment 18. The process of embodiment 14, wherein the ratio of the d50 particle size of the first alumina particles to the d50 particle size of the second alumina particles is from 1:8 to 1:15.

[0095] Embodiment 19. The process of embodiment 14, wherein the second alumina particles have a d50 particle size of about 10 to 200 microns.

[0096] Embodiment 20. The process of embodiment 14, wherein the second alumina particles have a d50 particle size of about 40 to 150 microns.

[0097] Embodiment 21. The process of embodiment 14, wherein the plurality of first alumina particles has a surface area of ​​from 1.0 m2 / g to 20.0 m2 / g.

[0098] Embodiment 22. The process of embodiment 14, wherein the plurality of first alumina particles has a surface area of ​​1.0 m2 / g to 5.0 m2 / g.

[0099] Embodiment 23. The process of embodiment 14, wherein the plurality of first alumina particles has a surface area of ​​between 1.0 m2 / g and 2.0 m2 / g.

[0100] Embodiment 24. The process of embodiment 14, wherein the plurality of second alumina particles has a surface area of ​​0.01 m2 / g to 2.00 m2 / g.

[0101] Embodiment 25. The process of embodiment 14, wherein the plurality of second alumina particles has a surface area of ​​between 0.10 m2 / g and 0.50 m2 / g.

[0102] Embodiment 26. The process of embodiment 14, wherein the plurality of second alumina particles has a surface area of ​​0.14 m2 / g to 0.30 m2 / g.

[0103] Embodiment 27. The process of embodiment 14, wherein the second alumina particles consist essentially of fused alumina.

[0104] Embodiment 28. The process of embodiment 14, wherein the second alumina particles are comprised of fused alumina.

[0105] Embodiment 29. The process of embodiment 14, wherein the second alumina particles consist essentially of platelet alumina.

[0106] Embodiment 30. The process of embodiment 14, wherein the second alumina particles comprise platelet alumina.

[0107] Embodiment 31. The process of embodiment 14, wherein the second alumina particles consist essentially of platelet alumina and fused alumina.

[0108] Embodiment 32. The process of embodiment 14, wherein the second alumina particles consist of platelet alumina and fused alumina.

[0109] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. All patents and publications mentioned herein are incorporated by reference in their entirety.

[0110] When ranges are used herein to describe physical or chemical properties, such as, for example, molecular weight or chemical formula, all combinations and subcombinations of ranges and specific embodiments therein are intended to be included. The use of the term "about" when referring to a number or numerical range means that the number or numerical range referred to is an approximation within experimental variability (or within statistical experimental error), and thus the number or numerical range may vary. The variation is typically 0% to 5% of the stated number or numerical range.

[0111] The transitional phrases "comprising," "consisting essentially of," and "consisting of," when used in the appended claims in their original and amended forms, define the claims in terms of the exclusion of additional unrecited claim elements or steps, if any, from the claim. The term "comprising" is intended to be inclusive or open-ended and does not exclude any additional unrecited elements, methods, steps, or materials. The term "consisting of" excludes any elements, steps, or materials other than those specified in the claim, and in the latter case, excludes impurities normally associated with the specified materials. The term "consisting essentially of" limits the claim to the specified elements, steps, or materials and those that do not materially affect the basic and novel characteristics of the claimed invention. All compounds, compositions, formulations, and methods described herein that embody the present invention may, in alternative embodiments, be more specifically defined by any of the transitional phrases "comprising," "consisting essentially of," and "consisting of." The term "comprising" (and related terms such as "comprise" or "comprises" or "having" or "including") includes embodiments, such as, for example, an embodiment of any composition, method, or process that "consists of" or "consists essentially of" the recited features.

Claims

1. 1. A process for the manufacture of a ceramic article comprising a hard formation of alumina particles and a catalytically active metal in contact with said particles, said process comprising: (a) a known weight and d between 0.2 and 20 microns 50 providing a plurality of first alpha alumina particles having a particle size; (b) providing a plurality of second alpha alumina particles having a known weight and comprising fused alumina, said second alumina particles having a d diameter between 5 and 400 microns; 50 The first alumina particles have a particle size of d 50 Particle size and d of the second alumina particles 50 a ratio of a weight of the first alumina particles to a weight of the second alumina particles is 1:1 to 15:1; (c) mixing the first plurality of alpha alumina particles with the second plurality of alpha alumina particles to form a mixture, the particles being randomly distributed throughout the mixture; and (d) forming the mixture into a plurality of malleable articles; (e) heating the malleable articles to a sintering temperature of the first and second alumina particles to form each malleable article into a hard formation of alumina particles, the particles in each plurality of particles being randomly distributed throughout the hard formation; and depositing a catalytically active metal on the first and second alumina particles; The ceramic article comprises: (a) a hard formation of alumina particles comprising a plurality of first alumina particles and a plurality of second alumina particles, both plurality of particles being randomly distributed throughout the hard formation; 1) the second alumina particles have a test value of 5 atomic percent or less in a ZnI2 dye penetrant test, and the first alumina particles have a test value that is at least twice the test value of the second alumina particles, the test value being a concentration of iodine, the test value being determined by a procedure including introducing a 5 g sample of the ceramic article into 100 mL of ZnI2 solution (220 g ZnI2 in 1000 mL of water), placing the sample in a container under vacuum for 20 hours, removing the sample from the container, drying the sample, and detecting the concentration of iodine in the sample by EDS; 2) the hard formation having a total cross-sectional area, each of the plurality of particles occupying a portion of the total cross-sectional area, the cross-sectional area of ​​the second alumina particles being between 5% and 50% of the total cross-sectional area; (b) a catalytically active metal dispersed on said first and second alumina particles.

2. 2. The process of claim 1, wherein the ratio of the weight of the first alumina particles to the weight of the second alumina particles is from 1:1 to 10:

1.

3. 2. The process of claim 1, wherein the ratio of the weight of the first alumina particles to the weight of the second alumina particles is from 1:1 to 5:

1.

4. d of the first alumina particles 50 Particle size and d of the second alumina particles 50 2. The process of claim 1, wherein the ratio of particle size is from 1:5 to 1:

20.

5. d of the first alumina particles 50 Particle size and d of the second alumina particles 50 2. The process of claim 1, wherein the ratio of particle size is from 1:8 to 1:

15.

6. The second alumina particles have a d 50 The process of claim 1 having a particle size.

7. The second alumina particles have a d 50 The process of claim 1 having a particle size.

8. The plurality of first alumina particles are 1.0 m 2 / g to 20.0 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

9. The plurality of first alumina particles are 1.0 m 2 / g to 5.0 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

10. The plurality of first alumina particles are 1.0 m 2 / g to 2.0 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

11. The plurality of second alumina particles are 2 / g to 2.00 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

12. The plurality of second alumina particles are 0.10 m 2 / g to 0.50 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

13. The plurality of second alumina particles are 0.14 m 2 / g to 0.30 m 2 2. The process of claim 1 having a surface area of ​​1 / g.

14. The process of claim 1 , wherein the second alumina particles are comprised of fused alumina.

Citation Information

Patent Citations

  • JP1971027071B

  • New-type battery

    JP1986171071A

  • Production of alumina porous carrier

    JP1999043380A

  • Catalyst support for ethylene oxide

    JP2015504361A

Cited By

  • Ceramic article and method of making the same

    JP2025037983A